2012
DOI: 10.1016/j.alcohol.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone and LY255582 on ethanol maintenance, seeking, and relapse responding by alcohol-preferring (P) rats

Abstract: Research indicates opioid antagonists can reduce alcohol drinking in rodents. However, tests examining the effects of opioid antagonists on ethanol seeking and relapse behavior have been limited. The present study examined the effects of two opioid antagonists on ethanol maintenance, seeking, and relapse responding by alcohol-preferring (P) rats. Adult P rats were self-trained in two-lever operant chambers to self-administer 15% (vol/vol) ethanol on a fixed-ratio 5 (FR5) versus water on a FR1 concurrent schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
(92 reference statements)
2
15
0
Order By: Relevance
“…These doses used are based on previous reports (Corrigall and Coen 1991; Dhaher et al 2012; Le et al 1999). Vehicle and the two doses of naltrexone were administered in counterbalanced order with each test separated by at least 2 d, on which animals received daily dual access sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These doses used are based on previous reports (Corrigall and Coen 1991; Dhaher et al 2012; Le et al 1999). Vehicle and the two doses of naltrexone were administered in counterbalanced order with each test separated by at least 2 d, on which animals received daily dual access sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Naltrexone is a non-selective opioid receptor antagonist most commonly used to treat alcohol dependence (Heilig and Egli 2006), but it also can reduce smoking (King and Meyer 2000). It reduces alcohol SA in laboratory rodents (Bienkowski et al 1999; Dhaher et al 2012; Le et al 1999), but does not affect nicotine SA except at very high doses, calling into question the specificity of its effects on nicotine SA (Corrigall and Coen 1991; Liu et al 2009). In heavy drinkers that smoke, naltrexone may be more effective in reducing alcohol intake (Fucito et al 2012; King et al 2009).…”
mentioning
confidence: 99%
“…Pharmacological studies evaluating the acquisition of ethanol intake have been conducted under both home-cage drinking and operant self-administration conditions. As seen in Table 3, roles for the adrenergic (Froehlich et al, 2013a,b), cannabinoid (Gessa et al, 2005; Serra et al, 2001), GABAergic (GABRB: Colombo et al, 2002a; Orrù et al, 2005), opioid (Dhaher et al, 2012b; Sable et al, 2006), and serotonergic (Rodd et al, 2010; Rodd-Henricks et al, 2000a) systems have been implicated in the acquisition of ethanol intake. Of the selectively bred rat lines discussed here, only the P and sP rat lines have been used to examine acquisition of ethanol intake.…”
Section: Behavioral Models For Screening Treatment Compounds And/omentioning
confidence: 99%
“…Essentially, peripheral naltrexone, a pan-opioid antagonist, has been tested repeatedly (Coonfield, Kiefer, Ferraro, & Sinclair, 2004; Dhaher et al, 2012; June, Grey, et al, 1998; Sable, Bell, Rodd, & McBride, 2006) along with a study testing the effects of CeA microinjections (Foster et al, 2004). These publications all reported significant reductions in ethanol intake by male and female, adolescent and adult P rats using both home-cage and operant procedures.…”
Section: Some Neurochemical Neuropharmacological As Well As Neurmentioning
confidence: 99%
“…Another study reported that nalmefene microinjections into the NAcb, Hipp and VTA significantly reduced operant alcohol self-administration by adult female P rats (June et al, 2004). A study examining the acquisition, maintenance and relapse operant self-administration of ethanol by adult female P rats found that the mu opioid receptor (MOR) antagonist LY255582 significantly reduced all of these behaviors (Dhaher et al, 2012). Other studies examined the role of the delta opioid receptor (DOR) in mediating ethanol intake by adult P rats.…”
Section: Some Neurochemical Neuropharmacological As Well As Neurmentioning
confidence: 99%